2020
DOI: 10.1684/mrh.2021.0476
|View full text |Cite
|
Sign up to set email alerts
|

Dysmagnesemia in Covid-19 cohort patients: prevalence and associated factors

Abstract: Hypomagnesemia and hypermagnesemia could have serious implications and possibly lead to progress from a mild form to a severe outcome of Covid-19. Susceptibility of subjects with low magnesium status to develop and enhance this infection is possible. There is little data on the magnesium status of patients with Covid-19 with different degrees of severity. This study was conducted to evaluate prevalence of dysmagnesemia in a prospective Covid-19 cohort study according to the severity of the clinical manifestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 29 publications
(48 reference statements)
2
60
0
Order By: Relevance
“…Limitations of this study are: firstly, its retrospective and cross-sectional nature, which did not allow us to evaluate the longitudinal modifications of these biochemical parameters during disease progression and recovery; secondly, the relatively limited number of patients enrolled due to the strict and rigorous inclusion and exclusion criteria used; thirdly, the evaluation of not-corrected tCa levels since albumin levels were not available (although we included ionized calcium levels analysis); and finally, the lack of data on magnesium levels since the latter were sporadically reported to be decreased in COVID-19 patients [ 49 ]. However, it should be noted that hypomagnesemia generally increases PTH secretion and it could hardly explain the impaired compensatory response of PTH observed in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations of this study are: firstly, its retrospective and cross-sectional nature, which did not allow us to evaluate the longitudinal modifications of these biochemical parameters during disease progression and recovery; secondly, the relatively limited number of patients enrolled due to the strict and rigorous inclusion and exclusion criteria used; thirdly, the evaluation of not-corrected tCa levels since albumin levels were not available (although we included ionized calcium levels analysis); and finally, the lack of data on magnesium levels since the latter were sporadically reported to be decreased in COVID-19 patients [ 49 ]. However, it should be noted that hypomagnesemia generally increases PTH secretion and it could hardly explain the impaired compensatory response of PTH observed in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective research on a total of 459 confirmed cases found that in the 63 expired individuals magnesium levels on admission were significantly lower than in the 396 survivors (1.61 ± 0.19 vs. 1.81 ± 0.23 mg/dl, respectively) [ 78 ]. Quilliot et al [ 79 ] performed a detailed analysis of magnesemia and associated factors in a cohort of 300 patients. Among these, 48% had a magnesemia below 0.75 mmol/L, including 13% of severely hypomagnesemic patients (0.65 mmol/L) 1 ; on the other hand, a small proportion of patients (9.6%) was hypermagnesemic (> 0.95 mmol/L).…”
Section: Introductionmentioning
confidence: 99%
“…Despite all limitations, existing data seem to corroborate an association between deranged magnesium homeostasis and COVID-19. The occurrence of hypermagnesemia in ICU cases in the absence of nephropathy, evidenced by two studies [ 79 , 81 ], is an intriguing finding that might be related to rapid mobilization from soft tissues in patients with sepsis or to necrotic events due to microvascular thrombosis. Therefore, this finding may not necessarily be in contrast with data that indicate hypomagnesemia as a risk factor for developing complications.…”
Section: Introductionmentioning
confidence: 99%
“…Some published studies focused on macroelements in COVID-19 patients revealed alterations in the Mg, Ca, Na, K, and Cl levels. For example, Quilliot et al [ 186 ], who evaluated the prevalence of dysmagnesemia in COVID-19 patients, but not the relationship between magnesemia and patient prognosis, noted a significant decrease in the concentration of Mg in moderately versus critically ill subjects. They also found that hypomagnesemia was significantly higher in patients classified into the moderate group than in critically ill subjects, whereas the prevalence of high-level serum Mg concentrations was markedly elevated in critically ill COVID-19 patients [ 186 ].…”
Section: Covid-19: Elementsmentioning
confidence: 99%